Metrics Applicable for Evaluating Software at The Design Stage - Gruzdo, Iryna V.; Kyrychenko, Iryna V.; Tereshchenko, Glib Yu.; Shanidze, Nadiya A. (CEUR-WS, 2021)
The paper reviewed and analyzed the existing metrics used in the software evaluation process at the design stage. Discussed issues related to the selection and accounting of indicators affecting the evaluation of software at the design stage in the management of software development. The study of the metrics used to perform the evaluation of software at the design stage. Find conclusions about the use of the metrics examined in management practice. Proved the need to study the metrics described in the Rada standards governing the process of developing software.
Keywords: software; software evaluatıon; metrıcs; software qualıty; project type; software development management; complexıty; accountıng